Environmental Teaching Supported by Web 2.0-Based Digital Games for a Sustainable Life - Arslan, Kevser; Karakus, Neslihan (MDPI, 2024)
Students' ability to exhibit positive behavior towards their environment plays a major role in building a sustainable world in the future. It is important to offer students, who are the subjects of the digital age, a more interactive and customized technology-focused learning experience. This study aims to reveal how environmental education supported by digital games affects middle school students' knowledge, environmentally responsible behaviors, and levels of digital literacy for a sustainable life. The participants in the research comprised 54 students studying at the fifth-grade level of secondary school. The research was conducted with a pre-test-post-test control group quasi-experimental design, which was one of the quantitative research methods. In the research, environmental education based on digital games created with Web 2.0 tools was carried out. Study data were collected through an environmental knowledge test, an environmentally responsible citizen behavior scale, and a digital literacy scale. Study data were analyzed using appropriate statistical analysis using a statistical program. The research results revealed that environmental education supported by digital games is effective. It was determined that students' knowledge level, environmental behavior, and digital literacy scores increased. Based on the research results, it is recommended that digital games be used to achieve more qualified learning.
Keywords: environment; environmental teaching; digital; Web 2.0 applications; digital game; STUDENTS; SCIENCE; PERCEPTIONS; METAANALYSIS; CREATIVITY; EDUCATION; TEACHERS; Science & Technology - Other Topics; Environmental Sciences & Ecology